Sovereign Debt Restructuring : Recent Developments and Implications for the Fund's Legal and Policy Framework. (Policy Papers; Policy Paper ;, 2013)
his paper reviews the recent application of the Fund's policies and practices on sovereign debt restructuring. Specifically, the paper: -- recaps in a holistic manner the various policies and practices that underpin the Fund's legal and policy framework for sovereign debt restructuring, including on debt sustainability, market access, financing assurances, arrears, private sector involvement (PSI), official sector involvement (OSI), and the use of legal instruments; -- reviews how this framework has been applied in the context of Fund-supported programs and highlights the issues that have emerged in light of recent experience with debt restructuring; and -- describes recent initiatives in various fora aimed at promoting orderly sovereign debt restructuring, highlighting differences with the Fund's existing framework. Based on this stocktaking, the paper identifies issues that could be considered in further depth in follow-up work by staff to assess whether the Fund's framework for debt restructuring should be adapted: -- first, debt restructurings have often been too little and too late, thus failing to re-establish debt sustainability and market access in a durable way. Overcoming these problems likely requires action on several fronts, including (i) increased rigor and transparency of debt sustainability and market access assessments, (ii) exploring ways to prevent the use of Fund resources to simply bail out private creditors, and (iii) measures to alleviate the costs associated with restructurings; -- second, while creditor participation has been adequate in recent restructurings, the current contractual, market-based approach to debt restructuring is becoming less potent in overcoming collective action problems, especially in pre-default cases. In response, consideration could be given to making the contractual framework more effective, including through the introduction of more robust aggregation clauses into international sovereign bonds bearing in mind the inter-creditor equity issues that such an approach may raise. The Fund may also consider ways to condition use of its financing more tightly to the resolution of collective action problems; -- third, the growing role and changing composition of official lending call for a clearer framework for official sector involvement, especially with regard to non-Paris Club creditors, for which the modality for securing program financing commitments could be tightened; and -- fourth, although the collaborative, good-faith approach to resolving external private arrears embedded in the lending into arrears (LIA) policy remains the most promising way to regain market access post-default, a review of the effectiveness of the LIA policy is in order in light of recent experience and the increased complexity of the creditor base. Consideration could also be given to extending the LIA policy to official arrears.